Comparing the Financial Soundness of Banks in Egypt and Turkey via CAMELS Framework - Bakr, M. (2020)
This study analyzes the financial soundness of banks in Egypt and Turkey using data for the largest ten banks in each country for the period 2012 to 2019. Two CAMELS-based approaches are employed in this study. The first is a comparative analysis in which thirteen ratios are used to account for the CAMELS components. The second approach uses the FDIC’s methodology to compute an overall composite rating for the banking sector in each country. Both countries have similar Capital Adequacy and Equity to Total Assets ratios. Turkey outperformed Egypt when it comes to NPL ratio due to Egypt’s historic high NPL ratios, however, Egypt has a higher NPL coverage ratio. Egypt had a better (lower) CTI ratio, which is used as a proxy for management efficiency. Both countries had similar NIM and Interest to Deposits ratio. Earnings wise, Egypt recorded higher ROAA and ROAE. As for liquidity, Egyptian banks are much more liquid due to their extensive investments in governmental securities. The trends behind the ratios are quite different for each country. Egyptian banks performed the worst during earlier years in the sample and started to reflect improvement in later years up to 2019. The opposite is true for Turkey which outperformed Egypt in earlier years and started to show a deteriorating trend in later years in the sample. Egypt initially had a higher composite rating of “2” compared to Turkey’s rating of “3”. However, after adjusting these ratios according to rules applied by the Fed, both countries ratings were downgraded to “4” indicating underperformance and an urgent need to address weaknesses.